Pilot Projects in Water Management - Heleen Vreugdenhil; Jill Slinger; Wil Thissen; Philippe Ker Rault (Ecology and Society, 2010)
Pilot projects appear in many forms in policy making and management. In an effort to understand the nature and use of pilot projects and improve their effectiveness, we undertake a practice-based and theoretical study of the pilot project phenomenon. First, we examine the roles assigned to pilot projects in the policy development literature and explore their use in a Dutch water innovation platform. Second, we determine characteristics of pilot projects to deepen insights into the nature of the pilot project phenomenon and the dimensions useful in the design of pilot projects. Third, we identify three pilot types and nine ways to use a pilot project and we develop a Pilot Project Nonagon that can be used to assess pilot projects' uses and to compare stakeholders' perspectives on these uses. Fourth, we identify hurdles to diffusion of the knowledge developed from pilot projects and suggest strategies to overcome these. Lastly, we formulate a research agenda aimed at addressing the identified knowledge gaps.